SPICE modelling of photoluminescence and electroluminescence based current-voltage curves of solar cells for concentration applications - Alonso,Alvarez D; Ekins-Daukes,N (Journal of Green Engineering, 2016)
Quantitative photoluminescence (PL) or electroluminescence (EL) experiments can be usedto probe fast and in a non-destructive way the current-voltage (IV) characteristics ofindividual subcells in a multi-junction device, information that is, otherwise, not available.PL-based IV has the advantage that it is contactless and can be performed even in partlyfinished devices, allowing for an early diagnosis of the expected performance of the solarcells in the production environment. In this work we simulate the PL- and EL-based IVcurves of single junction solar cells to assess their validity compared with the true IV curveand identify injection regimes where artefacts might appear due to the limited in-planecarrier transport in the solar cell layers. We model the whole photovoltaic device as anetwork of sub-circuits, each of them describing the solar cell behaviour using the two diodemodel. The sub-circuits are connected to the neighbouring ones with a resistor, representingthe in-plane transport in the cell. The resulting circuit, involving several thousand subcircuits,is solved using SPICE.